PENGARUH JUMLAH PENDUDUK DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KOTA MAKASSAR - Yusuf, Muhammad Fadly (Universitas Teuku Umar, 2024)
This study analyzes the influence of population and workforce on economic growth in Makassar City between 2014 and 2023. Using multiple linear regression methods with secondary data, this study found that population does not have a significant influence on economic growth. This indicates that population growth has not been matched by an increase in the quality of human resources (HR) capable of driving economic output. Conversely, the workforce has a significant influence, meaning that the absorption of productive labor contributes significantly to the Gross Regional Domestic Product (GRDP). This research model explains that 73.2% of the variation in economic growth is influenced by these two variables. Based on these findings, it is recommended that the Makassar City government prioritize policies that focus on improving the quality of the workforce and creating jobs to optimize the demographic bonus and encourage sustainable economic growth.Keywords : Population, Workforce, Economic Growth